Mucinous cystadenoma of the pancreas associated with pancreatic pseudocyst. Issue 2 (6th February 2023) - Horiuchi, Atsushi; Akehi, Shun; Abe, Yousuke; Ichikawa, Nanako; Kawaharada, Sakura; Kitazawa, Sohei; Kitazawa, Riko
Abstract: Mucinous cystadenoma of the pancreas is considered as a premalignant lesion, and resection is recommended. The majority of pancreatic cystic lesions are pancreatic pseudocysts, so differentiation between mucinous cystadenoma and pseudocyst is frequently required. We report a rare case of mucinous cystadenoma of the pancreas coexisting with pseudocyst. A 43-year-old woman presented with abdominal pain. Imaging examinations showed a large cystic lesion in the tail of the pancreas, and distal pancreatectomy and splenectomy were performed. Pathological examination revealed that the majority of the cystic wall comprised thick collagen fibrous connective tissue, while part of the cystic wall represented a single layer of columnar, mucin-producing epithelium without atypia. Those findings suggested mucinous cystadenoma with an inflammatory pseudocyst. The mixture of mucinous cystadenoma and pseudocyst within the same cystic lesion appears to be very rare. Complete resection of the cystic lesion seems to allow an excellent prognosis.